2017
DOI: 10.1111/apt.14097
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: the diminishing returns of normalisation of the oesophageal mucosa

Abstract: hampered by the lack of correlation between symptom improvement and changes in physiologic measures such as gastric emptying studies.A new direction in functional dyspepsia is the concept that the duodenum may be the source of symptoms. Observational studies show an increased number of eosinophils in duodenal biopsies obtained from adults and children with functional dyspepsia. [2][3][4] Other studies have shown an increase in mast cells in the mucosa and evidence of inflammation in the sub-mucosal nerves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…We have read with great interest the editorial by Dr. Genta—an attempt to reconcile the short turnover time of the oesophageal squamous epithelium with the results of our study, which showed that complete “normalisation” of oesophageal histology takes at least a few years . The results obtained in the LOTUS study demonstrated that progressive improvement of oesophageal histology occurs over the course of 5 years, and the same phenomenon is observed with regard to the degree of epithelial proliferation assessed by Ki67.…”
Section: Proportions Of Successfully Treated Patients With Normal MIsupporting
confidence: 63%
“…We have read with great interest the editorial by Dr. Genta—an attempt to reconcile the short turnover time of the oesophageal squamous epithelium with the results of our study, which showed that complete “normalisation” of oesophageal histology takes at least a few years . The results obtained in the LOTUS study demonstrated that progressive improvement of oesophageal histology occurs over the course of 5 years, and the same phenomenon is observed with regard to the degree of epithelial proliferation assessed by Ki67.…”
Section: Proportions Of Successfully Treated Patients With Normal MIsupporting
confidence: 63%